Nghiên cứu chu kỳ dao động của lượng mưa ở Việt Nam - Điền, Nguyễn Hướng; Minh, Trần Công (Vietnam Journal of Earth Sciences, 2001)
Periodic characteristics of the monthly rainfall in the territory of Vietnam